Gallium nitride sintered body and method for producing same
By controlling the moldability and molding process of gallium nitride, carbon impurities in hot pressing are avoided, and a faster film formation speed and a lower carbon content sputtering film are achieved, solving the influence of carbon impurities in gallium nitride sintered body The problem of improving the uniformity and density of the sintered body.
Patent Information
- Application Number
- CN202380039244.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-27
AI Technical Summary
The gallium nitride sintered body is easily mixed with trace carbon during hot pressing, resulting in a high carbon content in the sputtering film, affecting the film formation speed and quality.
By controlling the moldability of gallium nitride, using powder with a Ga/(Ga+N) ratio exceeding 0.5 and sintered in a nitride atmosphere, avoiding hot pressing, and using uniaxial pressing and CIP molding to ensure that the molded body is at room temperature Forming to reduce the inclusion of carbon impurities.
A faster film formation speed and a lower carbon content sputtering film are achieved, which improves the uniformity and density of the sintered body, is suitable as a sputtering target, and enhances the film formation performance.
Smart Images

Figure BDA0005124733770000171 
Figure BDA0005124733770000191 
Figure BDA0005124733770000201
Abstract
Description
Technical Field
[0001] The present invention relates to a sintered body of gallium nitride, and further to a sintered body of gallium nitride suitable as a sputtering target. Background Art
[0002] Since it is cheaper than single-crystal gallium nitride, the sintered body of gallium nitride, that is, the polycrystal of gallium nitride, has been studied as a sputtering target for forming gallium nitride films. However, compared with single-crystal gallium nitride, the sintered body of gallium nitride needs to improve the high oxygen content, low strength, low density, etc., and therefore, improvements based on various studies have been studied so far. In particular, the moldability of gallium nitride is low. Therefore, in industry, the sintered body of gallium nitride is manufactured by pressurizing the gallium nitride powder filled in a molding mold made of carbon (C) and performing hot pressing treatment to simultaneously perform molding and sintering (for example, Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2020-75851 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] During the hot pressing process, a trace amount of carbon below the measurement limit may be mixed into the sintered body. As a result, the carbon content of a sputtered film obtained using the sintered body of gallium nitride produced by the hot pressing process tends to be high.
[0008] An object of the present invention is to provide a gallium nitride sintered body capable of forming a sputtered film at a faster film forming rate than a gallium nitride sintered body produced by hot pressing, and an industrial production method thereof, a sputtering target having the sintered body, and at least one of a film forming method using the sputtering target.
[0009] Solutions for solving problems
[0010] The inventors of the present invention have studied the aspect of sintering after forming gallium nitride, focusing on the formability of gallium nitride. As a result, it was found that by controlling the composition of gallium nitride within a specific range, the formability is significantly improved, thereby obtaining a gallium nitride molded body even without a heated atmosphere, and such a molded body can be sintered by a sintering method other than hot pressing. It was further found that the sintered body obtained by a sintering method other than hot pressing has a different structure from the conventional one, and is suitable as a sputtering target.
[0011] That is, the present invention is described in the claims, and the gist of the present disclosure is as follows.
[0012] [1] A sintered body of gallium nitride, wherein a standard deviation of porosity determined from a scanning electron microscope image of a cross section is 1.0% or less.
[0013] [2] The sintered body according to [1] above, wherein the average porosity is 25% or less.
[0014] [3] The sintered body according to [1] or [2] above, wherein the oxygen content is 0.4 atm % or less.
[0015] [4] The sintered body according to any one of [1] to [3] above, wherein the atomic weight ratio of gallium to the total of gallium and nitrogen is 0.5 or less.
[0016] [5] The sintered body according to any one of [1] to [4] above, wherein the bulk density is 4.0 g / cm 3 above.
[0017] [6] A method for producing a sintered body according to any one of [1] to [5], comprising: a step of molding a powder containing gallium nitride and metal gallium and having a Ga / (Ga+N) ratio exceeding 0.5 to obtain a molded body; and a step of sintering the molded body in a nitriding atmosphere.
[0018] [7] The manufacturing method according to [6] above, wherein the step of obtaining the molded body is a step of obtaining a primary molded body by uniaxially pressing the powder, and subjecting the primary molded body to CIP molding.
[0019] [8] The manufacturing method according to [6] or [7] above, wherein the nitriding atmosphere contains one or more gases selected from the group consisting of a nitrogen and hydrogen mixed gas, ammonia gas, hydrazine gas, and alkylamine gas.
[0020] [9] A gallium nitride molded body having a Ga / (Ga+N) ratio exceeding 0.5.
[0021]
[10] A sputtering target comprising the sintered body according to any one of [1] to [5] above.
[0022]
[11] A method for producing a sputtered film, using the sputtering target described in
[10] above.
[0023] Effects of the Invention
[0024] According to the present disclosure, it is possible to provide a gallium nitride sintered body capable of forming a sputtered film at a faster film forming rate than a gallium nitride sintered body produced by hot pressing, an industrial production method thereof, a sputtering target having the sintered body, and at least one of a film forming method using the sputtering target. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram showing the observation field in the measurement of average porosity and SDρ. DETAILED DESCRIPTION
[0026] Hereinafter, the present disclosure will be described with reference to an example of the embodiment.
[0027] [Sintered body of gallium nitride]
[0028] The sintered body of the present embodiment is a gallium nitride sintered body having a standard deviation of porosity determined from a scanning electron microscope image of a cross section of 1.0% or less.
[0029] The present embodiment relates to a sintered body of gallium nitride. A sintered body of gallium nitride (GaN) is a sintered body with gallium nitride as the main component (matrix, parent phase), and is a polycrystal of gallium nitride. It is a sintered body mainly composed of gallium nitride, a so-called gallium nitride sintered body. However, the sintered body of the present embodiment may also contain components other than gallium nitride, such as metallic gallium.
[0030] The sintered body of the present embodiment may contain doping elements. As doping elements for forming an n-type semiconductor, one or more selected from the group consisting of silicon (Si), germanium (Ge), tin (Sn) and lead (Pb) can be cited. In addition, as doping elements for forming a p-type semiconductor, one or more selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), vanadium (Ba), zinc (Zn) and cadmium (Cd) can be cited. In addition, as doping elements for forming an LED of any color, at least any one of aluminum (Al) and indium (In) can be cited. As the main doping elements contained in the sintered body of the present embodiment, one or more selected from the group consisting of silicon, magnesium, aluminum and indium can be cited.
[0031] The content of the doping element can be a sufficiently small amount relative to gallium nitride, and also varies depending on the type of the doping element. For example, the content of the doping element can be 0 atm% or more, and 25 atm% or less, 15 atm% or less, 1 atm% or less, or 0.1 atm% or less.
[0032] An ideal sintered body has no pores, so the porosity is 0%. However, a realistic sintered body contains pores. The porosity of the sintered body of the present embodiment exceeds 0%. The sintered body is preferably dense, and the average porosity can be 1% or more or 10% or more. In order to show mechanical properties suitable for use as a sputtering target, the average porosity of the sintered body of the present embodiment can be 25% or less or 20% or less.
[0033] The standard deviation of the porosity of the sintered body of the present embodiment obtained from the scanning electron microscope image of the cross section (hereinafter also referred to as "SDρ") is 1.0% or less, preferably 0.8% or less. If SDρ exceeds this value, the structure of the sintered body, especially the structure inside the sintered body, becomes uneven. When such a sintered body is used for sputtering, particles are easily generated, and the film formation speed is slowed down. SDρ is ideally preferably 0%. However, a real sintered body has pores, and the distribution of the pores and the porosity are biased. The SDρ of the sintered body of the present embodiment can be, for example, more than 0%, 0.1% or more, or 0.3% or more.
[0034] Furthermore, one of the reasons why the sintered body of the present embodiment has such an SDρ is that the amount of carbon mixed in as an impurity is small. That is, carbon is difficult to sinter, and even below the detection limit, the sintering of gallium nitride is hindered by the presence of carbon. In contrast, the sintered body of the present embodiment has a lower carbon content than conventional sintered bodies, so sintering becomes easier. As a result, it is believed to have a uniform organizational structure. This can also be confirmed from the fact that the carbon content of the sputtering film obtained using the sintered body of the present embodiment becomes smaller.
[0035] In this embodiment, the average porosity and SDρ can be obtained by observing the cross section of the sintered body using a scanning electron microscope (hereinafter, also referred to as "SEM"). SEM observation is performed using a general SEM (e.g., JSM-IT800, manufactured by JEOL Ltd.), and the cut surface obtained by cutting the sintered body can be used as the observation surface. Before SEM observation, the cut surface can also be subjected to ion milling, and then low-temperature ion milling to produce an observation surface. Figure 1 As shown, the observation field of view is set to the center of the cut surface (observation field of view 1; Figure 1 (101)), by observing the straight line of field of view 1 ( Figure 1 The part of the midline segment AA') 150 μm away from the end of the observation field 1 (observation field 2; Figure 1 (102)), and a portion on the straight line that is 1150 μm away from the observation field in the direction opposite to the direction from the observation field 1 toward the observation field 2 (observation field 3; Figure 1 (103)) A total of 3 fields of view are sufficient. The observation field of view is a rectangular area of 250 μm × 180 μm. That is, Figure 1 The figure shows a case where three rectangular observation fields of 250 μm×180 μm are arranged in a straight line at intervals of 150 μm. The conditions for SEM observation are as follows.
[0036] Accelerating voltage: 5kV
[0037] Observation magnification: 500 times
[0038] Next, the obtained SEM observation images are analyzed using general image analysis software (e.g., Image-Pro10, manufactured by Hakuto Co., Ltd.) to detect pores and their areas. 2 ] It can be detected from the image after the SEM observation image is binarized. The porosity of each SEM observation image can be calculated by the following formula.
[0039] Porosity [%] = {pore area [μm 2 ] / SEM observation area [μm 2 ]}×100
[0040] The average porosity can be determined by calculating the porosity at three measurement points, for example, the observation field 1, observation field 2, and observation field 3, and then calculating the average value. 2 The above surface part.
[0041] In addition, SDρ may be obtained from the standard deviation of the porosity at each measurement point.
[0042] The bulk density of the sintered body of this embodiment is preferably 4.0 g / cm 3 Above or 4.2g / cm 3 By having such a bulk density, the sintered body of this embodiment can easily have sufficient strength when used as a sputtering target. The higher the bulk density, the more preferred it is. For example, 5.0 g / cm 3 Below, 4.8g / cm 3 Below or 4.7g / cm 3 the following.
[0043] In the present embodiment, the “density” is a bulk density measured by a method in accordance with JIS R1634, and the pretreatment may be performed by a vacuum method using distilled water.
[0044] The average grain size of the sintered body of the present embodiment is arbitrary as long as it is 0.1 μm or more or 0.2 μm or more, and can be 0.5 μm or less or 0.3 μm or less, for example.
[0045] In the present embodiment, the average grain size can be obtained by scanning electron microscope-electron backscatter diffraction (hereinafter also referred to as "SEM-EBSD") of the cross section of the sintered body. SEM-EBSD observation can be performed using a general EBSD (e.g., Symmetry, Oxford Instruments) on a SEM observation diagram obtained by the same method as the average porosity. The conditions for EBSD observation are shown below.
[0046] Accelerating voltage: 15 kV
[0047] Sample tilt: 70 degrees
[0048] Tilt correction: 0°
[0049] Measurement magnification: 500 times
[0050] Step size: 0.2 μm
[0051] The position where the crystal orientation is tilted by more than 5° is regarded as a grain boundary, and the area surrounded by the grain boundary is regarded as a grain. The diameter of the circle equivalent to the area of each grain can be calculated as the grain diameter. The grains observed in three fields of view (for example, 100,000 to 30,000 grains per field of view) obtained by the same method as the average porosity are observed by SEM-EBSD, and the average grain diameter in each field of view is calculated by image analysis. The average is taken as the average grain diameter.
[0052] In the sintered body of the present embodiment, the atomic weight ratio of gallium to the total of gallium and nitrogen ([mol / mol]; hereinafter also referred to as "Ga / (Ga+N) ratio") is 0.5 or less. With such a Ga / (Ga+N) ratio, the gallium contained in the sintered body of the present embodiment is substantially only gallium nitride. That is, the metal Ga is completely nitrided, and the sintered body does not contain metal Ga. Ga / (Ga+N) is preferably less than 0.5 or less than 0.49, and can be 0.45 or more or 0.47 or more.
[0053] The oxygen content of the sintered body of the present embodiment is preferably 0.4 atm% or less or 0.2 atm% or less. The sintered body of the present embodiment is preferably free of oxygen (i.e., the oxygen content is 0 atm%), and examples thereof include an oxygen content of 0 atm% or more, more than 0 atm%, 0.01 atm% or more, or 0.1 atm% or more. If such an oxygen content is used, the film obtained by using it as a sputtering target tends to show characteristics more suitable for uses such as light-emitting diodes and power devices. As specific oxygen contents, examples thereof include 0.1 atm% or more and 0.3 atm% or less, and further 0.13 atm% or more and 0.2 atm% or less.
[0054] The composition of the sintered body of the present embodiment can be regarded as a composition represented by the following formula.
[0055] 100 = W Ga [Mass %] + W O [Mass %] + W N [Mass %] + W X [Mass %] (1)
[0056] (1)W Ga , WO , W N and W X are the mass proportions of gallium, oxygen, nitrogen and doping elements in the sintered body. O and W N W is a value measured by a thermal decomposition method in which a sintered body is thermally decomposed using a general oxygen and nitrogen analyzer (e.g., LECO ON736, manufactured by Leco Corporation). X is the value determined by glow discharge mass spectrometry. Ga According to W O , W N and W X The measured value of is the value obtained by formula (1).
[0057] The oxygen content is a value obtained from the following formula (2).
[0058] Oxygen content [atm%]
[0059] =(W O / M O ) / {(W Ga / M Ga )+(W N / M N )+(W O / M O )+(W X / M X )}(2)
[0060] (2) In the formula, M O The atomic weight of oxygen is 16.00 [g / mol], M Ga The amount of gallium in oxygen: 69.72 [g / mol], and M N The atomic weight of nitrogen is 14.01 [g / mol]. X It is the atomic weight of the doping element, for example, the atomic weight of silicon is 28.09 [g / mol], the atomic weight of magnesium is 24.31 [g / mol], the atomic weight of aluminum is 26.98 [g / mol], and the atomic weight of indium is 114.82 [g / mol].
[0061] The Ga / (Ga+N) ratio is a value obtained from the following formula (3).
[0062] Ga / (Ga+N) ratio=(W Ga / M Ga ) / {(W Ga / M Ga )+(W N / M N )} (3)
[0063] In order to exhibit mechanical properties suitable for a sputtering target, the Vickers hardness of the sintered body of the present embodiment is preferably 100 HV or more or 150 HV or more. A moderately high Vickers hardness is sufficient, and examples thereof include 1000 HV or less, 300 HV or less, or 250 HV or less.
[0064] In the present embodiment, the Vickers hardness may be a value measured by a method in accordance with JIS B 7725. The Vickers hardness may be obtained by pressing a pyramidal indenter on a sintered body with a force of 1 kgf, observing the indentation formed with a microscope, and calculating the surface area of the indentation from the horizontal distance of the diagonal line.
[0065] For the same reason, the flexural strength of the sintered body of the present embodiment is preferably 20 MPa or more, more preferably 30 MPa or more, further preferably 50 MPa, and may be 150 MPa or less, 100 MPa or less, or 60 MPa or less.
[0066] In the sintered body of this embodiment, the upper and lower limits of parameters such as average porosity, SDρ, packing density, average grain size, Ga / (Ga+N) ratio, oxygen content, content of doping elements, Vickers hardness and flexural strength can be any combination of the above.
[0067] The sintered body of the present embodiment can be used for known uses of sintered bodies of gallium nitride, and is particularly preferably used as a sintered body for a sputtering target.
[0068] [Method for producing sintered body]
[0069] The method for producing a sintered body of the present embodiment is a method for producing a sintered body comprising the following steps: a step of molding a powder containing gallium nitride and metal gallium and having a Ga / (Ga+N) ratio exceeding 0.5 to obtain a molded body; and a step of sintering the molded body in a nitriding atmosphere. Thus, a sintered body of any shape can be industrially produced without being restricted by the shape of a molding die of a sintering furnace.
[0070] The powder (hereinafter also referred to as "raw material powder") used in the step of molding a powder containing gallium nitride and metallic gallium and having a Ga / (Ga+N) ratio exceeding 0.5 to obtain a molded body (hereinafter also referred to as the "molding step") can be any powder containing gallium nitride and metallic gallium, for example, a mixed powder of gallium nitride and metallic gallium.
[0071] The Ga / (Ga+N) ratio of the raw powder exceeds 0.5, preferably is greater than 0.51. Since the raw powder has such a composition, it is easy to form even without a heating atmosphere. In the present embodiment, one of the reasons why the raw powder can be formed even without a heating atmosphere, especially without an atmosphere in which molding and sintering are performed simultaneously, is that due to the presence of metallic gallium between the particles of gallium nitride, the fluidity of the particles increases and the bonding strength between the particles increases. As a result, a molded body with high shape stability can be obtained compared to a molded body that does not substantially contain metallic gallium and consists only of gallium nitride. The Ga / (Ga+N) ratio may be less than 0.6 or less than 0.55.
[0072] The raw material powder may be a powder composed of gallium nitride and metal gallium. In order to impart properties corresponding to the application such as semiconductor properties, it may also contain doping elements. As doping elements, it may include compounds containing one or more selected from the group consisting of silicon (Si), germanium (Ge), tin (Sn), lead (Pb), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), zinc (Zn), indium (In) and aluminum (Al), and compounds containing one or more selected from the group consisting of silicon, magnesium, indium and aluminum.
[0073] In order to obtain a sintered body showing n-type semiconductor characteristics, the raw powder may contain one or more selected from the group of silicon, germanium, tin and lead. In addition, in order to obtain a sintered body showing p-type semiconductor characteristics, the raw powder may contain one or more selected from the group of magnesium, calcium, strontium, barium and zinc. In order to obtain a sintered body with a changed band gap, the raw powder may contain at least one of indium and aluminum. The doping element contained in the raw powder can be appropriately selected according to the target sintered body, and its content can be the same as the content of the doping element in the sintered body of the present embodiment described above. That is, the content of the doping element does not change before and after sintering, and the content of the doping element contained in the sintered body is equal to the content of the element in the raw powder provided for sintering.
[0074] In order to reduce the oxygen content of the obtained sintered body, the oxygen content of the raw material powder is preferably 1 atm% or less, 0.5 atm% or less, or 0.3 atm% or less. The raw material powder is preferably free of oxygen (i.e., the oxygen content is 0 atm%), but may contain oxygen as long as it does not affect the characteristics of the obtained sintered body. The oxygen content of the raw material powder may be 0.005 atm% or more or 0.01 atm% or more.
[0075] The oxygen content of the raw material powder in the present embodiment is a value measured according to the method of JIS H1695.
[0076] Since the oxygen content is easy to reduce, the specific surface area of the raw material powder is preferably 0.01 m 2 / g or more, and preferably 1.5 m 2 / g or less than 0.8m 2 / g.
[0077] The specific surface area of the raw material powder in the present embodiment is a value measured according to the method of JIS R1626:1996.
[0078] Since the strength of the obtained sintered body is likely to be high, the light packing density of the raw material powder is preferably 1.0 g / cm 3 Above or 1.4g / cm 3 Because the moldability is easy to improve, the light packing density is less than 3.0g / cm 3 Or 2.5g / cm 3 That's it.
[0079] The light bulk density of the raw material powder in the present embodiment is a value measured by a method in accordance with JIS Z2504.
[0080] The average particle size of the raw material powder is preferably 1 μm or more, 5 μm or more, or 9 μm or more, and is preferably 150 μm or less, 100 μm or less, or 80 μm or less.
[0081] The average particle size of the raw material powder in this embodiment is an average value obtained by measuring the equivalent circle diameter obtained from the area of 1200±400 primary particles in a scanning electron microscope (hereinafter also referred to as “SEM”) observation image obtained under the following conditions.
[0082] Accelerating voltage: 10 kV
[0083] Observation magnification: 50 times to 5000 times
[0084] The SEM observation in the measurement of the average particle size may be performed using a general SEM (eg, VE-9800, manufactured by KEYENCE Co., Ltd.) Alternatively, only primary particles whose entire particles can be confirmed in the SEM observation image may be measured, and a plurality of SEM observation images may be used to obtain the above number of particles.
[0085] In the molding process, the raw material powder is molded to obtain a molded body. The molding method may be any molding method that can obtain a molded body having a desired shape, and at least any one of uniaxial pressing and cold isostatic pressing (hereinafter also referred to as "CIP") molding can be exemplified. A molded body (compressed powder body) is obtained by these molding methods. In the molding process, it is preferred that the raw material powder is molded without heating it, and the raw material powder is preferably molded at room temperature (25±10°C). It is preferred that the Ga / (Ga+N) ratio does not change before and after molding. That is, it is preferred that the Ga / (Ga+N) ratio of the raw material powder is the same as the Ga / (Ga+N) ratio of the molded body. In the molding method in which the Ga / (Ga+N) ratio does not change before and after molding, the shape freedom of the molded body is high.
[0086] As a particularly preferred molding, a primary molded body is obtained by uniaxially pressing the raw material powder, and CIP molding is performed on the primary molded body. The conditions for uniaxial pressing can be any conditions that can obtain a primary molded body with a degree of shape retention that does not cause defects when provided for CIP molding. In addition, according to such a molding method, the Ga / (Ga+N) ratio does not change before and after molding. For example, the pressure of uniaxial pressing is greater than 10MPa or greater than 25MPa, and can be 200MPa or less or 300MPa or less. CIP molding can be any condition that can obtain the molded body described later, for example, the pressure of CIP molding can be 100MPa or greater than 200MPa, and 400MPa or less or 500MPa or less.
[0087] The manufacturing method of this embodiment includes a step of sintering the molded body in a nitriding atmosphere (hereinafter also referred to as a "sintering step"). By providing a molded body having a certain shape as a sintered object, a sintered body having an arbitrary size and shape derived from the size and shape of the molded body can be obtained. Furthermore, compared with the conventional sintering method in which molding and sintering are performed integrally by hot pressing (hereinafter also referred to as "HP") treatment, a larger sintered body can be obtained.
[0088] The molded body provided for the sintering step can be a molded body having the same composition as the raw material powder, and a molded body having a Ga / (Ga+N) ratio exceeding 0.5 and containing gallium nitride and metallic gallium can be mentioned. The Ga / (Ga+N) ratio of the molded body is preferably 0.51 or more. The Ga / (Ga+N) ratio of the molded body can be 0.6 or less or 0.55 or less.
[0089] The raw material powder of this embodiment does not need to be molded in a heated atmosphere, so a gallium nitride molded body having a desired shape can be obtained. The shape of the molded body can be any desired shape, and can be one or more selected from the group consisting of a disk, a cylinder, a rectangle, a polyhedron, and a cone, or any other shape corresponding to the purpose and use.
[0090] The size of the molded body is arbitrary, but the raw material powder of this embodiment can be molded in a non-heating atmosphere such as room temperature, so it can also be obtained in the form of a large molded body. For example, as a molded body suitable for a precursor of a sintered body used as a sputtering target, a plate-shaped or disk-shaped molded body can be cited. The moldability of the raw material powder is high, so the molded body can also be made into a molded body with an area of 100mm 2 Above or 1,000mm 2 The area of the surface can be exemplified as 100,000 mm 2 Below, 20,000mm 2 Below or 5,000mm 2 the following.
[0091] As a specific shape of the molded body, a diameter of 5 mm can be exemplified. 2 Above or 10mm 2 Above, and 300mm 2 Below or 150mm 2 The following circular plate shape.
[0092] The measured density of the molded body is 3.0 g / cm 3 Above or 3.6g / cm 3 Above, in addition, 5.8g / cm 3 Below or 5.5g / cm 3 the following.
[0093] The measured density of the molded article in the present embodiment is a value measured by a method in accordance with JIS Z8807.
[0094] In the sintering process, the molded body is sintered in a nitriding atmosphere. By sintering in a nitriding atmosphere, the metal gallium in the molded body is nitrided to become gallium nitride. Thus, a sintered body having the Ga / (Ga+N) ratio of the present embodiment is obtained. Conventionally, a sintered body (polycrystalline) of gallium nitride is sintered by HP treatment, and molding and sintering are performed simultaneously. In the HP treatment, since the raw material powder is filled in the molding die and then pressurized, the shape of the obtained molded body is restricted by the shape of the molding die, and impurities from the molding die are easily mixed. In contrast, in the present embodiment, sintering is performed without pressurizing the molded body to which a shape is given in advance, so a molding die is not required during sintering. That is, the shape of the molded body does not depend on the molding die provided by the HP device. Thus, the shape freedom of the molded body becomes high. Furthermore, carbon molding dies are mainly used in industrial HP treatment. In contrast, in the manufacturing method of the present embodiment, impurities from the molding die, especially carbon (C), can be prevented from mixing. As a result, when a sputtering film is formed using a sputtering target having a sintered body of the present embodiment, a sputtering film having a lower carbon content can be obtained. From the viewpoint of avoiding the mixing of impurities, especially the mixing of carbon, the manufacturing method of the present embodiment preferably does not have an HP treatment, especially an HP treatment with a carbon molding die.
[0095] The nitriding atmosphere in this embodiment refers to an atmosphere in which a nitriding reaction is performed, in particular, an atmosphere in which a nitriding reaction is performed and an oxidation reaction is not performed. Therefore, the nitriding atmosphere includes not only a nitrogen atmosphere, but also an atmosphere containing other than nitrogen. As the nitriding atmosphere, an atmosphere containing at least any one of nitrogen and a nitrogen compound can be exemplified, preferably one or more selected from the group consisting of a nitrogen and hydrogen mixed gas, ammonia, hydrazine gas, and an alkylamine gas, more preferably at least any one of ammonia and a nitrogen and hydrogen mixed gas, and even more preferably ammonia.
[0096] As particularly preferred nitriding atmospheres, there can be cited a circulating atmosphere, a nitrogen compound circulating atmosphere, and an ammonia circulating atmosphere. By becoming a circulating atmosphere, that is, an atmosphere in which an atmospheric medium such as a nitrogen-containing compound gas flows, the nitridation reaction of metal gallium is promoted. As a result, the composition of the obtained sintered body becomes more uniform. The circulating atmosphere only needs to be a state in which there is flow in the atmospheric medium, for example, a flow rate of 0.1 mL / min or more or 1 L / min or more can be cited. On the other hand, the flow rate can be appropriately set according to the performance of the molded body and the sintering furnace to be processed, and can be exemplified as less than 20 L / min or less than 10 mL / min.
[0097] The sintering step is preferably performed without pressurizing the molded body (the object to be sintered), and is preferably performed without applying a molding pressure to the molded body.
[0098] The holding temperature in the sintering process can be any temperature for sintering gallium nitride. Furthermore, unlike the HP process, the molded body provided in the sintering process has a certain shape. Therefore, compared with the sintering method such as the HP process that simultaneously performs molding and sintering, even a sintered body with a high density can be obtained at a lower holding temperature. Therefore, as the sintering temperature, 1100°C or less, 1050°C or less, or 1000°C or less can be exemplified. On the other hand, the holding temperature can be 800°C or more, 900°C or more, or 950°C or more.
[0099] The holding time at the holding temperature varies depending on the holding temperature, the size of the molded body, the performance of the sintering furnace used, etc. At the above-mentioned holding temperature, the holding time can be exemplified as more than 1 hour and less than 20 hours, and further can be exemplified as more than 2 hours and less than 10 hours.
[0100] In the manufacturing method of this embodiment, the upper and lower limits of parameters such as the Ga / (Ga+N) ratio, the surface area of the molded body, the measured density of the molded body, the flow rate of the atmosphere medium, the holding temperature and the holding time can be any combination of the above.
[0101] [Sputtering target]
[0102] Next, a sputtering target including a sintered body according to the present embodiment will be described.
[0103] A sputtering target including the sintered body of the present embodiment (hereinafter, also referred to as “the target of the present embodiment”) is a sputtering target in which the sintered body of the present embodiment is bonded to a support body via a bonding layer.
[0104] The shape of the target of the present embodiment is arbitrary, and at least any one of a flat plate shape and a cylindrical shape, and a shape suitable for the application can be exemplified.
[0105] The target of the present embodiment bonds (i.e., bonds) the sintered body of the present embodiment to a support body through a bonding layer. The bonding layer only needs to be composed of a solder containing one or more selected from the group of tin, indium and zinc. Since the electrical conductivity and thermal conductivity of the target are likely to be high, the bonding layer is preferably composed of a solder containing indium. It should be noted that, in the case where the bonding layer is a solder containing indium, the target of the present embodiment may have a layer (hereinafter also referred to as a "barrier layer") for improving wettability between the sintered body of gallium nitride and the bonding layer. As a result, the indium wettability of the sintered body is improved, and as a result, the bonding between the sintered body and the bonding layer becomes more secure. The barrier layer only needs to be composed of a component with high wettability to indium, preferably at least one of nickel and chromium.
[0106] On the other hand, since the cost increases, the target of the present embodiment preferably does not have a layer containing tungsten (W), and particularly preferably does not have a layer containing tungsten as a barrier layer.
[0107] The support body in the target of the present embodiment is preferably one or more selected from the group consisting of copper, stainless steel and titanium. In addition, the shape of the support body can be any desired shape corresponding to the shape of the sintered body of the present embodiment, and at least one of a flat plate and a cylindrical shape and a shape suitable for the purpose can be exemplified.
[0108] [Film Forming Method]
[0109] Next, a method for producing a sputtered film (film forming method) using the target of the present embodiment will be described.
[0110] The sputtered film is formed on the substrate by sputtering using the target of this embodiment. Thus, the sputtered film can be formed, and further, a gallium nitride film can be formed, and further, a gallium nitride thin film can be formed.
[0111] For example, the sputtering method can include one or more selected from the group consisting of DC sputtering, pulsed DC sputtering, RF sputtering, AC sputtering, DC magnetron sputtering, RF magnetron sputtering and ion beam sputtering, and preferably at least one of DC magnetron sputtering and RF magnetron sputtering can be included.
[0112] The sputtering gas can be any gas used for sputtering, and an inert gas can be mentioned, and at least one of argon and nitrogen can be mentioned. When sputtering is performed using the target of the present embodiment, the surface of the obtained sputtered film tends to become smooth, so the sputtering gas is preferably a nitrogen-containing gas, preferably a mixed gas of argon and nitrogen. The mixed gas preferably has an excess of nitrogen, and the nitrogen / (nitrogen+argon) partial pressure ratio [Pa / Pa] is preferably greater than 0.5, 0.7 or 0.9.
[0113] The flow rate of the sputtering gas is 5 ml / min or more or 10 ml / min or more and 100 ml / min or less or 70 ml / min or less.
[0114] The gas pressure of the sputtering gas may be 0.05 Pa or more or 0.1 Pa or more, and 3 Pa or less or 2 Pa or less.
[0115] In order to stably generate plasma, the discharge power density during sputtering is 0.1 W / cm 2 Above or 0.3W / cm 2 Above, in addition, 5W / cm 2 The following will do.
[0116] The substrate can be appropriately selected according to the target film and the stack of substrates (hereinafter also referred to as a "stack"), and for example, one or more selected from the group consisting of a glass substrate, an aluminum oxide substrate, a silicon substrate, a gallium nitride substrate, an aluminum nitride substrate and a silicon carbide substrate can be cited, and further, at least any one of an aluminum oxide substrate, a silicon substrate and a gallium nitride substrate can be cited.
[0117] The sputtering method and conditions can be appropriately selected according to the target sputtering film.
[0118] The temperature of the substrate during film formation by sputtering (hereinafter also referred to as "film formation temperature") is arbitrary, and may be 10° C. or more or 20° C. or more, and 800° C. or less. When the film formation speed is increased, the film formation temperature is 100° C. or more or 300° C. or more, and may be 800° C. or less or 500° C. or less.
[0119] The sputtering time (hereinafter also referred to as "film forming time") can be appropriately set according to the sputtering conditions, the size of the substrate, and the thickness of the target sputtered film, for example, more than 1 minute or more than 10 minutes and less than 5 hours or less than 1 hour.
[0120] Example
[0121] Hereinafter, the present disclosure will be described by way of examples, however, the present disclosure is not limited thereto.
[0122] (Average porosity and SDρ)
[0123] The sintered body was cut to expose the cut surface at the center of the sintered body, and then the cut surface was processed by low-temperature Ar ion milling to produce a measurement surface. Figure 1 The cross-section was observed by SEM in the following manner at observation fields 1, 2, and 3. The SEM observation was performed using a general SEM (device name: JSM-IT800, manufactured by JEOL Ltd.) under the following conditions.
[0124] Accelerating voltage: 5kV
[0125] Observation magnification: 500 times
[0126] Next, the obtained SEM observation images were binarized using general image analysis software (Image-Pro10, manufactured by Hakuto Co., Ltd.), and image analysis was performed to detect pores and their areas. The porosity of the SEM observation image corresponding to each observation field was calculated by the following formula.
[0127] Porosity [%] = {pore area [μm 2 ] / SEM observation area [μm 2 ]}×100
[0128] The average porosity was calculated by calculating the porosity of each of the three observation fields and then calculating the average value. SDρ was calculated from the standard deviation of the porosity of each observation field.
[0129] (Average grain diameter)
[0130] The SEM observation images of three fields obtained by the same method as the measurement of the average porosity and SDρ were observed using a general EBSD device (device name: Symmetry, manufactured by Oxford Instruments, Inc.) EBSD observation was performed under the following conditions.
[0131] Accelerating voltage: 15 kV
[0132] Sample tilt: 70 degrees
[0133] Tilt correction: 0°
[0134] Measurement magnification: 500 times
[0135] Step size: 0.2 μm
[0136] The position where the crystal orientation is tilted by more than 5° is regarded as a grain boundary, and the area surrounded by the grain boundary is regarded as a grain. The diameter of the circle equivalent to the area of each grain is calculated as the grain diameter. The average value of the grains observed in 3 fields of view obtained by the same method as the average porosity is taken as the average grain diameter.
[0137] (Bulk density)
[0138] The bulk density of the sintered body was measured by a method in accordance with JIS R 1634. The pretreatment was performed by a vacuum method using distilled water.
[0139] (composition)
[0140] The oxygen [mass %] and nitrogen mass ratio [mass %] of the sintered body were measured by inert gas fusion-infrared absorption method using an oxygen-nitrogen analyzer (device name: LECO ON736, manufactured by Leco). Based on the obtained oxygen and nitrogen mass ratios, the gallium mass ratio was calculated by the above formula (1), the oxygen content [atm %] was calculated by the above formula (2), and the Ga / (Ga+N) ratio was calculated by the above formula (3).
[0141] (Vickers hardness)
[0142] The Vickers hardness of the sintered body was measured by a method in accordance with JIS Z 2244. Five points of measurement were performed on one measurement sample, and the average value was taken as the Vickers hardness.
[0143] (Determination of flexural strength)
[0144] The three-point bending strength of the sintered body was measured by a method in accordance with JIS R 1601. The measurement was performed twice, and the average value was taken as the bending strength.
[0145] (Carbon content)
[0146] The carbon content of the sputtered film was measured using secondary ion mass spectrometry (SIMS) at a depth of 50 nm from the film surface.
[0147] Example 1
[0148] Prepare 8g of mixed powder of metal gallium and gallium nitride with a Ga / (Ga+N) ratio of 0.52, and fill it into a rectangular mold with a length of 10mm and a width of 40mm. After filling, uniaxial pressing is performed at a pressure of 100MPa to obtain a primary molded body. The primary molded body is cold isostatically pressed at a pressure of 300MPa to obtain a CIP-treated body.
[0149] The CIP-treated body was placed on an alumina setter and sintered in an atmosphere furnace under the following conditions to obtain a sintered body of this example.
[0150] Heat treatment atmosphere: Ammonia circulation atmosphere
[0151] (Ammonia flow rate 6000mL / min)
[0152] Keeping temperature: 980℃
[0153] Holding time: 5 hours
[0154] Example 2
[0155] A sintered body of this example was obtained in the same manner as in Example 1 except that 8 g of a mixed powder of metal gallium and gallium nitride having a Ga / (Ga+N) ratio of 0.51 was used.
[0156] Example 3
[0157] A sintered body of this example was obtained in the same manner as in Example 1 except that 8 g of a mixed powder of metal gallium and gallium nitride having a Ga / (Ga+N) ratio of 0.53 was used.
[0158] Example 4
[0159] A sintered body of this example was obtained in the same manner as in Example 1 except that 8 g of a mixed powder of metal gallium and gallium nitride having a Ga / (Ga+N) ratio of 0.54 was used.
[0160] Comparative Example 1
[0161] 8 g of mixed powder of metal gallium and gallium nitride with a Ga / (Ga+N) ratio of 0.48 was filled into a rectangular mold of 10 mm long and 40 mm wide. After filling, uniaxial pressing was performed at a pressure of 100 MPa and 180 seconds. However, defects such as notches and cracks occurred when the mold was removed, and a primary molded body could not be obtained.
[0162] It was confirmed from the Examples and Comparative Examples that the mixed powder rich in metallic gallium having a Ga / (Ga+N) ratio of 0.5 or more has higher moldability than the powder rich in gallium nitride and can be molded even at a low temperature.
[0163] Comparative Example 2
[0164] 300 g of a gallium nitride mixed powder having a Ga / (Ga+N) ratio of 0.48 was filled into a carbon press die having a diameter of 130 mm, and the mixture was hot-pressed under the following conditions.
[0165] Heat treatment atmosphere: vacuum
[0166] Heating rate: 200℃ / hour
[0167] Maintaining temperature: 1060℃
[0168] Holding time: 3 hours
[0169] Pressing pressure: 40MP a
[0170] Cooling speed: 200℃ / hour
[0171] After the HP treatment, a sintered body of gallium nitride was obtained from a carbon press die, and this was used as a sintered body of this comparative example.
[0172] The results of Examples and Comparative Examples are shown in the following table.
[0173] [Table 1]
[0174]
[0175] ※“-” in the table means not measured
[0176] It was confirmed that the SDρ of the sintered body of the example was 1.0% or less, and the structure of the sintered body was more uniform than that of the sintered body of Comparative Example 2. The average grain size was 2.5 μm for Example 1, 2.1 μm for Example 3, 1.6 μm for Example 4, and 2.4 μm for Comparative Example 2.
[0177] Example 5
[0178] The sintered body of this example was obtained in the same manner as in Example 1 except that the heat treatment atmosphere was an ammonia flow atmosphere (ammonia flow rate 2000 mL / min). The Ga / (Ga+N) ratio of the sintered body of this example was 0.48, and the oxygen content was 0.23 atm%.
[0179] Example 6
[0180] A sintered body of this example was obtained in the same manner as in Example 2 except that the holding temperature was 930° C. and the holding time was 1 hour. The sintered body of this example had a Ga / (Ga+N) ratio of 0.49 and an oxygen content of 0.29 atm%.
[0181] Example 7
[0182] A sintered body of this example was obtained in the same manner as in Example 3 except that the holding temperature was 1030° C. and the holding time was 1 hour. The sintered body of this example had a Ga / (Ga+N) ratio of 0.49 and an oxygen content of 0.10 atm%.
[0183] The oxygen content of the sintered body of Example 1 was 0.17 atm %, whereas the oxygen content of the sintered body of Example 5 was 0.23 atm %. It was confirmed that the oxygen content decreased because reduction was more likely to proceed as the ammonia flow rate increased.
[0184] The oxygen content of the sintered body of Example 2 was 0.16 atm %, whereas the oxygen content of the sintered body of Example 6 was 0.29 atm %. Therefore, it was confirmed that the oxygen content decreased as the sintering holding temperature increased.
[0185] The oxygen content of the sintered body of Example 3 was 0.15 atm%, while the oxygen content of the sintered body of Example 7 was 0.10 atm%, so it can be confirmed that the oxygen content decreases with the increase of the sintering holding temperature regardless of the ammonia flow rate (6000 mL / min or 2000 mL / min). It is believed that the decrease in oxygen content caused by the increase in the holding temperature has a greater impact than the increase in oxygen content caused by the decrease in the ammonia flow rate.
[0186] Example 8
[0187] A sintered body of this example was obtained in the same manner as in Example 1 except that 95 g of a mixed powder of metal gallium and gallium nitride having a Ga / (Ga+N) ratio of 0.52 was used and filled into a 60 mm×60 mm rectangular mold.
[0188] Example 9
[0189] A sintered body of this example was obtained in the same manner as in Example 1 except that 380 g of a mixed powder of metal gallium and gallium nitride having a Ga / (Ga+N) ratio of 0.52 was used and filled into a circular mold having a diameter of 135 mm.
[0190] The evaluation results of the sintered bodies obtained in these Examples are shown in the following table.
[0191] [Table 2]
[0192]
[0193] From the above table, it can be confirmed that in the embodiment, not only a circular sintered body but also a rectangular sintered body can be produced. 2 Above, further 10000mm 2 Large sintered bodies above.
[0194] [Film formation evaluation]
[0195] The sintered bodies obtained in Example 8 and Comparative Example 2 were cut into disks with a diameter of 101 mm. Indium solder was applied to the processed sintered bodies and bonded to a copper backing plate to prepare sputtering targets.
[0196] Using the obtained sputtering target, sputtering was performed under the following conditions to form a gallium nitride film (sputtered film).
[0197] Discharge method: RF sputtering
[0198] Substrate: Al2O3
[0199] Sputtering gas: nitrogen
[0200] Sputtering gas flow rate: 50sccm
[0201] Sputtering pressure: 0.5Pa
[0202] Discharge power density: 2.5W / cm 2
[0203] Film forming temperature: 25°C
[0204] Film forming time: 60 minutes
[0205] The results of the film formation evaluation are shown in the following table. However, the carbon content of Example 9 was not measured and is indicated by "-".
[0206] [Table 3]
[0207]
[0208] The sintered body of Example 8 is the same as the sintered body of Example 1 except for the sintered body size, and SDρ is smaller than the sintered body of Comparative Example 2. The film formation speed of the target of Example 8 is 1.9 times or more relative to that of the target of Comparative Example 2, and it can be confirmed that a faster film formation speed is shown. In addition, the carbon content of the gallium nitride film obtained by the target of Example 8 is less than 1 / 3 of that of the gallium nitride film obtained by Comparative Example 2, and it can be confirmed that a sputtered film with a low carbon content is obtained.
[0209] It should be noted that this application is based on Japanese Patent Application (Japanese Patent Application No. 2022-095341) filed on June 13, 2022, the entirety of which is incorporated by reference. In addition, all references cited herein are incorporated as a whole.
[0210] Description of Reference Numerals
[0211] 100 sintered body
[0212] 101 Observation Field 1
[0213] 102 Observation Field 2
[0214] 103 Observation Field 3
Claims
1. A sintered body of gallium nitride, wherein: The standard deviation of the porosity determined from the scanning electron microscope image of the cross section was 1.0% or less.
2. The sintered body according to claim 1, wherein the average porosity is 25% or less.
3. The sintered body according to claim 1 or 2, wherein the oxygen content is 0.4 atm % or less.
4. The sintered body according to any one of claims 1 to 3, wherein The atomic weight ratio of gallium to the total of gallium and nitrogen is 0.5 or less.
5. The sintered body according to any one of claims 1 to 4, which has a bulk density of 4.0 g / cm 3 above.
6. A method for producing a sintered body according to any one of claims 1 to 5, comprising: a step of compacting a powder containing gallium nitride and metal gallium and having a Ga / (Ga+N) ratio exceeding 0.5 to obtain a compact; and a step of sintering the compact in a nitriding atmosphere.
7. The manufacturing method according to claim 6, wherein: The step of obtaining the molded body is a step of obtaining a primary molded body by uniaxially pressing the powder, and subjecting the primary molded body to CIP molding.
8. The manufacturing method according to claim 6 or 7, wherein: The nitriding atmosphere includes one or more gases selected from the group consisting of a nitrogen and hydrogen mixed gas, an ammonia gas, a hydrazine gas, and an alkylamine gas.
9. A gallium nitride molded body having a Ga / (Ga+N) ratio exceeding 0.
5. 10 . A sputtering target comprising the sintered body according to claim 1 . 11 . A method for producing a sputtered film, using the sputtering target according to claim 10 .